PERBEDAAN SUBSTRAT DAN DISTRIBUSI JENIS MANGROVE (STUDI KASUS : HUTAN MANGROVE DI KOTA TARAKAN) - Indah, Rosaria; Jabarsyah, Abdul; Laga, Asbar (Jurnal Harpodon Borneo, 2010)
The purpose of this research are to know tpe of soil pursuant to type of mangrove, to know correlation of soil to species composition distribution of mangrove.  Benefit of this research are to give information regarding how far plant of mangrove in region coastal area of Tarakan city can grow at certain substrat.  To government of Tarakan city as supporter information regarding readyly seed stok of mangrove needed to area of mangrove matching with place growing.  Equiping researchs which have there and as reference to researchers here in after to do research concerning mangrove.  The result of this research are distribution type of mangrove for Sonneratia sp in area of forest mangrove in Old Amal Beach 100% known to have type of soil dominant sand with its mean proportion of its, sandy 96,00%, silt 2,37%, clay 0,31%. Distribution of Rhizopora sp in area of forest mangrove Gusher 90,16% known to have type of soil dominant sandy clay with its mean proportion of its, sandy 87,03%, silt 10,8%, clay 2,09%.  Distribution of Bruguiera sp in area of forest mangrove Gusher 47,77% known to have type of soil dominant sand with its mean proportion of its, sandy 93,73%, silt 5,19%, clay 0,46%. Its correlation for the type of Avicennia sp, Sonneratia sp, and Bruguiera sp show happened relation but donot so sliver. While Rhizopora sp show happened relation so sliver. Keywords : Soil, distribution type of mangrove, Correlation.